Kajian Ontologis Dan Epistemologis - Fadhil Akbar (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This paper aims to explore the basic concepts of ontological and epistemological studies on religion in society (social reality) and religion in normative and sociological perspectives (texts). This type of research is a literature review using the sociology of religion and history approach which will reveal some basic concepts about religion from a normative and sociological perspective. Religious Studies with a normative approach leads to aspects of the main and original teachings of God in which there is no reasoning of human thought. Whereas Religious Studies with a sociological approach leads to ways of socializing, culture and personality with things that can influence it